2012
DOI: 10.1016/j.limno.2012.07.004
|View full text |Cite
|
Sign up to set email alerts
|

What governs macrophyte species richness in kettle hole types? A case study from Northeast Germany

Abstract: a b s t r a c tKettle holes are small, pond-like, depressional wetlands in young moraine landscapes. They mostly undergo a wet-dry cycle and have a high potential for biological species diversity. However, their biodiversity and habitat function is often greatly impacted by surrounding intensive agricultural land use practices.In this study, we used statistical analysis of a large data set from the federal state of Brandenburg (Northeast Germany) to characterise the macrophyte species richness of kettle holes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 45 publications
(68 reference statements)
3
44
0
1
Order By: Relevance
“…However, the quantity of matter received into lakes from their catchments is not proportional to their volume (Piotrowicz et al, 2006;Schindler, 2009). In intensively managed agricultural landscape these small bodies of water play the role of matter-traps (Gerke et al, 2010), biogeochemical barriers (Szpakowska & _ Zyczyńska-Bałoniak, 1994;Lischeid & Kalettka, 2012), as well as hotspots for high biodiversity (Oertli et al, 2002;Williams et al, 2004;Pätzig et al, 2012). Research on small water bodies located in the natural and anthropogenically transformed landscape confirms significant variation in the quality of water (Joniak et al, 2007;Gałczyńska & Kot, 2010) and bottom sediments .…”
Section: Introductionmentioning
confidence: 99%
“…However, the quantity of matter received into lakes from their catchments is not proportional to their volume (Piotrowicz et al, 2006;Schindler, 2009). In intensively managed agricultural landscape these small bodies of water play the role of matter-traps (Gerke et al, 2010), biogeochemical barriers (Szpakowska & _ Zyczyńska-Bałoniak, 1994;Lischeid & Kalettka, 2012), as well as hotspots for high biodiversity (Oertli et al, 2002;Williams et al, 2004;Pätzig et al, 2012). Research on small water bodies located in the natural and anthropogenically transformed landscape confirms significant variation in the quality of water (Joniak et al, 2007;Gałczyńska & Kot, 2010) and bottom sediments .…”
Section: Introductionmentioning
confidence: 99%
“…Because site conditions differ among the kettle holes, the region Uckermark is a hotspot for biodiversity of endangered amphibian species (Berger et al 2011), large branchiopods (Gołdyn et al 2012) and aquatic macrophytes (Pätzig et al 2012;Altenfelder et al 2014). Drainage, fertilization and herbicide use in surrounding arable fields during the past few decades, however, has led to a severe decline in diversity of both plant species (Altenfelder et al 2014) and amphibians (Berger et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…With the aid of the Shannon diversity index obtained for zooplankton inhabiting large water ecosystems in Russia (Habelman & Haldna, 2014) or ponds in Belgium (De Bie et al, 2012), we demonstrated that our small water bodies were characterised by slightly higher diversity. This indicates habitat quality and regional distinctiveness (Pätzig et al, 2012). The wide range of the zooplankton diversity index in the investigated ponds reflected a high level of habitat heterogeneity.…”
Section: Discussionmentioning
confidence: 74%